Iowa Birdline update, March 7, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for March 7, 1994. Highlights include Mountain Bluebird, Greater Prairie-Chicken and Varied Thrush. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed